Healthcare-seeking behavior among pregnant women in the Chinese hierarchical medical system: a cross-sectional study - Guihao Liu; Yunlian Xue; Zhenzhu Qian; Liuna Yang; Yunbin Yang; Qingshan Geng; Xin Wang (BMC, 2019)
Abstract Background Hierarchical medical systems are common in developed countries, but it's not optimistic in China. This study aimed to identify the factors affecting healthcare-seeking behavior among pregnant women in Guangdong, China. Methods We conducted a cross-sectional, observational survey, developed using the Andersen's behavioral model. Pregnant women were randomly selected using a two-stage, stratified, random sampling method from hospitals in Guangdong, China. A multinomial logistic regression was used to identify statistically significant variables from aspect of environmental, demographic and pregnancy characteristics associated with pregnant women seeking healthcare at primary, secondary or tertiary hospitals. Results A total of 1393 pregnant women returned the survey after attending 1 of 12 hospitals within 4 cities of the Guangdong province: 537 (38.5%) of the respondents attended a primary hospital, 437 (31.4%) a secondary hospital, and 419 (30.1%) a tertiary hospital. Women attending primary hospitals were more likely to live closer to the hospital, live rurally, and be educated to a lower level. Several factors were significantly associated with attendance at a secondary vs a primary hospital: the woman's perceived necessity to seek maternal healthcare (OR 1.73, 95% CI [1.1,2.74]), the woman's choice of delivery hospital (OR 1.45, 95% CI [1.01,2.07]), or urban living (OR 1.39, 95% CI [1.03,1.88]). Characteristics associated with attendance at a tertiary vs a primary hospital were: a history of pregnancy complications (OR 2.35, 95% CI [1.43,3.86]), travel to the hospital by public transport/taxi (OR 2.09/2.67, 95% CI [1.35,3.22]/ [1.45,4.92]), urban living (OR 1.58, 95% CI [1.14,2.18]), or a planned current pregnancy (OR 1.53, 95% CI [1.07,2.19]). Conclusion Medical needs and convenience both play a role in the choice of hospital for antenatal care, and impact on equity utilization of health services. Pregnant women without risk factors and with higher levels of education should be a target population for guiding to choose a more proper level of hospital.